Technologijų dalyko turinio kaita ir mokinių mokymo(si) pasiekimai. - Juralovič, Marijana (Social Education / Socialinis Ugdymas, 2021)
A person’s inclinations and abilities are determined by nature and upbringing. A child’s development is inextricably linked to both of these factors. Nature is the most important factor influencing gender-specific behavior, but experience, practice, and interaction with others also affect neurons and brain connections. The female brain performs all cognitive functions like the male brain, but using other brain links. Studies show that the genetic susceptibility of men’s and women’s brains to environmental influences differs. Changes in educational paradigms - teaching (impact), interaction and learning - are directly related to the teacher’s work style, teaching goals, methods, teaching/learning environment, teacher-student interaction, as well as educational documents regulating general education. According to the IEA TIMSS, IEA PIRLS, MESS (Ministry of Education, Science and Sport), NMPT, NEC studies, over the 17 (seventeen) (2002–2018) years, there are significant differences in the learning achievements of girls and boys in the country and in the world. In Lithuania, girls tend to achieve better learning outcomes (especially there is a large gap between boys and girls reading skills). There is currently a lack of subject didactics research to help understand how to effectively teach different subjects to students of different genders. In Lithuania, as in most European countries, there are areas of education where it is necessary to take more care of girls’ learning opportunities, but in other areas the boys’ learning is more of a concern. Technology lessons and studies are a great medium to encourage students’ (young people’s) creative beginnings, develop their creativity, positive thinking, implement moral values and strengthen motivation for science. The subject matter of technology in various aspects has been studied by different scientists for many years. Looking at the “history” of the subject of technology, it can be stated that it lost the interest of students during the change of the curriculum of the subject. The noble goal of “preserving the subject” in various ways: reorganizing the curriculum in university and school learning programs. Creating only mixed groups of students, did not preserve the subject of technology at university and reduced learning motivation among pupils and students. The subject of technology is the only thing whose change in content has helped to refine the natural different teaching (learning) of boys and girls and to draw attention to the differences in their teaching/learning achievements in other subjects as well. These differences in teaching learning have existed in Lithuanian and world schools for many years. In order to find out the problems of the subject of technology, a questionnaire survey of students and teachers was conducted in 2018. A total of 800 students were interviewed: 456 girls and 344 boys, 21 teachers: 7 male and 14 female. Pupils from 5th, 6th, 7th, 8th, 9th, 10th grade from different Lithuanian schools participated in the study. The survey found that 87.4% of students support a technology program that takes into account the “nature” and learning differences of boys and girls. Only 12.6% of students do not support this program. Therefore, it can be concluded that their “nature” which influences teaching is important to students. The following problem areas of the technology subject were also identified: 1) textile program (23.5%), programs of construction materials are evaluated the lowest: (32.5%). A higher proportion of students (62.1%) have stated that learning motivation is stronger and the results are better when technology is being learned in different gender groups. Coordinated efforts should be made in Lithuania and around the world to encourage boys and girls to reach their full potential. Experience in OECD countries shows that some action can be taken to close the gap in learning outcomes between girls and boys. There is a need to look for ways to get boys and girls interested in learning subjects. Reduce the study load in subjects, give up homework or replace homework with creative projects or long-term tasks. Stop forming a “fear” attitude towards science for students who are being prepared for their twelfth grade exams from the first grade. Take into account the preparation of the school olympics. In all subjects, the tasks of the olympics must be designed purposefully: for the age group and class of the students, taking into account the subject programs. To achieve this goal, teachers shouldn’t teach students,,in advance” because children’s brain circuits have a certain period of puberty and are psychologically unprepared for information and workload that are more complex than students are able to understand. Introduce a reading and writing skills program in schools that would improve students’ comprehension and writing skills and the quality of teaching/learning. While updating the curriculum that seeks to develop scientific potential in higher education institutions that train teachers on this topic.